Format Ulang Masa Depan Islam: Review atas Model Politik Pengetahuan pada Sunnī dan Shī‘Ī - Muchammad Helmi Umam (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2016)
This article explores how Sunnī and Shī‘ī Muslims develop knowledge politics in accordance with their unique thought environments. This research discovers tentative evidence that the Muslim political leadership model plays an important part in the dynamics of Muslim society by employing a qualitative literature method with a descriptive-argumentative approach. Normatively, Sunnis and Shiites are similar, yet historically, there are strategic disparities. The notions of wilāyat al-‘ulamā’ in Sunnī and wilāyat al-faqīh in Shī‘ī have the similar content in terms of the politics of knowledge in forming leadership standards, but they have different methodologies for gaining knowledge and abilities. This article confirms that there are no normative issues with Islamic leadership and Islamic politics. Differences in perspectives on Islamic politics exist only in the model of political knowledge and technical state competencies. Furthermore, the constructive achievements of Islamic politics arise only when the leader chooses scientific leadership. In the golden age of medieval Islamic civilization, for example, the politics of knowledge spawned the culture of knowledge. During the period, the political leadership was successful in developing a wide range of information goods and useful tools for the people.